2021
DOI: 10.1063/5.0040926
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and stabilization of a kilohertz laser-plasma accelerator

Abstract: Laser–plasma acceleration at kilohertz repetition rates has recently been shown to work in two different regimes with pulse lengths of either 30 fs or 3.5 fs. We now report on a systematic study in which a large range of pulse durations and plasma densities were investigated through continuous tuning of the laser spectral bandwidth. Indeed, two laser–plasma accelerator (LPA) processes can be distinguished, where beams of the highest quality, with a charge of 5.4 pC and a spectrum peaked at 2–2.5 MeV, are obtai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…We point out that these quasimonoenergetic bunches can be suitable for many high repetition applications, although further studies on directional and long-term stability are still needed. 59,60 We have also shown that the processes that give rise to such bunches in TW and sub-TW SM-LWFA do not have the typical DLA energy gain, nor the expected DLA signatures are verified on their electrons. 41 Instead, the bunch characteristics and the acceleration history are compatible with those of the blowout LWFA.…”
Section: F Summary and Conclusionmentioning
confidence: 86%
See 2 more Smart Citations
“…We point out that these quasimonoenergetic bunches can be suitable for many high repetition applications, although further studies on directional and long-term stability are still needed. 59,60 We have also shown that the processes that give rise to such bunches in TW and sub-TW SM-LWFA do not have the typical DLA energy gain, nor the expected DLA signatures are verified on their electrons. 41 Instead, the bunch characteristics and the acceleration history are compatible with those of the blowout LWFA.…”
Section: F Summary and Conclusionmentioning
confidence: 86%
“…These sources have also been pointed for the irradiation of biological samples, ultrafast imaging, and femtosecond x-ray generation. 14,59…”
Section: Quasimonoenergetic Beam Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma electrons are then self-injected and accelerated into the wakefield, forming high quality, quasimonoenergetic electron beams [17][18][19] . While most LPAs are driven by laser pulses containing many optical cycles, few-cycle pulses can now be used to excite wakefields and accelerate electrons [20][21][22][23] . In this case, the usual framework of a cycle-averaged ponderomotive force 24 is not sufficient to describe the interaction.…”
mentioning
confidence: 99%
“…In our experiments, we are able to detect and control this CEP-dependent pointing of the accelerated electron beam, see illustration in figure 1. Our LPA is driven by laser pulses as short as 1.3 cycles (< 4 fs FWHM in intensity) 16,21,22 . Two active feedback loops allow for stabilization and control of the CEP (see Methods).…”
mentioning
confidence: 99%